LATERAL LINE SENSORY CANAL SYSTEM IN CYNOGLOSSUS SEMIFASCIATUS DAY - Seshappa, G (Indian Journal of Fisheries, 2011)
This paper gives an illustrated description of the normal lateral linesensory canal system in Cynoglossus semifasciatus D?y, and also of certainabnormalities noticed in the species, with a special reference to certain casesof partial ambicolour?tion and albinism.Eight sensory canals are noticed in the species. These are: the cephalodorsal,the dorsolateral, the supra-orbital, the mediodorsal, the pre-orbital,the pre-opercular and the mandibulo-opercular lines and the supra-orbitalcommissure.The main abnormaUties that were noticed related to: (1) the occiu*-rence of breaks in the course of the canals with or without the extension ofthe broken ends, (2) growth of offshoots, extension of canals beyond theirusual end limits and various combinations of these, (3) absence of the preorbitalline and the shortening of the cephalo-dorsal and the supra-orbital.lines.